2018
DOI: 10.1159/000487845
|View full text |Cite
|
Sign up to set email alerts
|

Physical Exhaustion Induced Variations in Event-Related Potentials and Cognitive Task Performance in Young Adults

Abstract: Background/Aims: Physical exhaustion is not always peripheral, and it is the brain that causes the sensation of fatigue either due to decrease of metabolic resources or due to central activation process that regulates attention and performance. This study was undertaken to observe the variations in event-related potentials (ERPs) and cognitive performance after an exhausting physical exercise. Methods: A total of 60 healthy young adult subjects were included in the study. The study was conducted in 2 phases wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Executive functions include planning, problem solving, flexibility, inhibition, multitasking, and working memory [18]. A negative effect of high blood lactate levels induced by an exhaustive exercise or with an intravenous infusion of a lactate solution has been found for attentional processes [3,5,6,8,10,19]. Regarding the working memory, a negative effect of exhaustive exercise on both non-spatial working memory and motor working memory was found [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Executive functions include planning, problem solving, flexibility, inhibition, multitasking, and working memory [18]. A negative effect of high blood lactate levels induced by an exhaustive exercise or with an intravenous infusion of a lactate solution has been found for attentional processes [3,5,6,8,10,19]. Regarding the working memory, a negative effect of exhaustive exercise on both non-spatial working memory and motor working memory was found [9].…”
Section: Introductionmentioning
confidence: 99%
“…The effects of acute physical exercise on the cognitive performances of an adult individual are still under discussion [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. The existing literature tends to highlight a positive relationship if the exercise is of sub-maximal intensity, while the effects seem to be negative for exhaustive exercises [19][20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Research on the impact of physical exertion on cognitive processes has provided inconsistent findings. Evidence have shown that moderate intensity exercise may have a positive effect on cognitive task performance (e.g., Kumar et al, 2012); however, physical exhaustion has been linked to reduced response accuracies in cognitive tasks (Itagi et al, 2018). Overall, the relationship between exercise and cognitive performance has been characterized as complex (Lambourne and Tomporowski, 2010) and may differ as a function of timing (during or following exercise), exercise modality (e.g., cycling vs. running) and intensity (moderate vs. vigorous).…”
Section: Discussionmentioning
confidence: 99%
“…We recorded the Bruce protocol level and total exercise time at the end of the exercise immediately. Presence of any three of the following four conditions was a criterion for the termination of exhaustive exercise [45,46]. (1) Behavior: difficulty in breathing with profuse sweating; (2) blood pressure changes: systolic blood pressure of ≥150 mm Hg and diastolic blood pressure of ≥75 mm Hg; (3) heart rate: a maximum heart rate of ≥180 bpm; (4) RPE level: reaching an RPE level of 18.…”
Section: High-intensity Exercise Protocolmentioning
confidence: 99%